OPPORTUNITIES AND THREATS TO INCREASE ROOM OCCUPANCY HOLIDAY INN RESORT BALI BENOA - Ni Wayan Puspa Astika Kencana; I Wayan Basi Arjana; Made Sudiarta (Journal of Applied Sciences in Travel and Hospitality, 2018)
This research is conducted to know the opportunities and threats to increase room occupancy at Holiday Inn Resort Bali Benoa. The research method is mixed methods research, of which the data collected in this research were done through observation, interviews, questioner and study documentation. The analysis technique that used is SWOT analysis. Based on SWOT analysis it is showed that Holiday Inn Resort Bali Benoa has 5 variable of opportunities and 4 variable of threats. The result of SWOT identification show there are develop the market segmentation and marketing mix that we used for target, push promotion through social media, website, email blast method to introduce Holiday inn Resort Bali Benoa worldwide. Furthermore selling the higher room category to the free individual traveler and minimize allotment for the group series at the resort.